Stochastic Analysis of A Two-Identical Unit Cold Standby System with Maximum Repair Time and Correlated Busy and Idle Times of the Operator Cum Repairman (Journal of Informatics and Mathematical Sciences, 2009)
This paper is considered with modelling and analysis of a two identical unit standby system with the concept ofrest of the operator cum repairman. Here, the concept of correlation between busy time and idle time of theoperator cum repairman is considered which is not, generally, seen in the literature. If the repairman is notable to repair a failed unit within a specified time limit (pre fixed) then the failed unit is replaced by a replacement facility. The different measures of economic importance are obtained by using regenerative point technique. The MTSF and profit function have also been studied throughgraphs in respect of various parameters in a particular case when repair time distribution is taken as exponential.
Keywords: Stochastic Analysis